High fatigue levels among psychiatric outpatients – the validity of the Danish Patient Reported Outcomes Measurement Information System Fatigue Short-Form (PROMISF-SF) - Ragnar Klein Olsen; Sidse M. Arnfred; Christina Madsen; Oliver Rumle Hovmand (Journal of Patient-Reported Outcomes)
Abstract Background Patient Reported Outcomes Measurement Information System Fatigue Short-Form (PROMIS-F-SF) is a self-administered, patient reported outcome (PRO) designed to assess fatigue in healthy and clinical populations and for tracking progress during treatment for disorders complicated with fatigue. Methods Patients in the Mental Health Service Outpatient Clinics and healthy volunteers were invited to complete a survey, which included the Danish translation of the PROMIS-F-SF, the Chalder Fatigue Scale (CFS-11), and measures of depression and anxiety. We conducted a confirmatory factor analysis of the previously suggested single-factor structure of the instrument. We furthermore evaluated the construct validity of the PROMIS-F-SF by means of its relationship with the CFS-11. Finally, we evaluated the utility of the PROMIS-F-SF to identify patient-status by conducting receiver operating characteristic curves. Results 70 healthy volunteers and 62 patients completed the instruments. The PROMIS-F-SF had a average fit to the previously reported single-factor structure. Cronbach’s alpha and McDonald’s omega showed good internal reliability (α = 0.96, ωtotal = 0.97). PROMIS-F-SF score was positively correlated with the CFS-11 (r =.76) and it correlated highly with depression (r =.78) and anxiety (r =.74) score. The optimal cut-off point in the ROC-analyses was 15, which yielded a sensitivity of 89% and a specificity of 67% in the prediction of patient status. Conclusions Level of fatigue among psychiatric outpatients is high in patients with psychiatric illness, compared to levels measured in healthy volunteers. The Danish PROMIS-F-SF shows good psychometric properties in this combined sample of healthy adults and psychiatric patients with non-psychotic disorders and it is recommended as PRO measure for psychiatric populations. Examination of psychometric properties in patient populations with somatic disorder could be a natural next step.